Peran LMID dalam Mendorong Partisipasi Politik Mahasiswa di Kota Bandar Lampung - Rhaina Rifka Nefindia; Najua Fauzani; Annita Yunida Fikri; Teki Prasetyo Sulaksono; Ana Mentari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to examine the role and contributions of the youth organization Liga Mahasiswa Indonesia untuk Demokrasi (LMID) in promoting youth political participation and advocating for social justice values. Using a descriptive qualitative approach, data were collected through direct interviews with the General Chairperson of LMID Bandar Lampung. The findings indicate that LMID envisions a democratic Indonesia free from all forms of oppression, with a mission to engage students and the wider community in grassroots struggles. The organization’s activities include advocacy for people’s rights, political education, literacy development through book and film discussions, and educational programs such as learning centers for children in conflict-affected areas. LMID is also active in gender equality issues and frequently leads social actions concerning women’s rights. The organization adopts a democratic structure, though it faces internal challenges in reconciling differing opinions among members. These findings highlight the strategic importance of political education and grassroots organizing in shaping a critical, participatory, and pro-people youth generation. This study concludes that youth organizations like LMID hold significant potential in fostering political awareness and strengthening democracy at the local level.